The Role of Educational Institutions in the Spatial Development of Historical Areas (Case study Bosra city). - المهنا, سليمان; أبودحلوش, قبس (Latakia University Journal -Engineering Sciences Series, 2022)
Since the seventies of the last century, the United Nations has issued repeated calls to strengthen the relationship between heritage and education, for its awareness of the importance of the role that education plays in preserving the tangible and intangible heritage and protecting the popular heritage. Universities also play an important role in deepening awareness of the importance of heritage among students and learners, as it helps them to realize The importance of archaeological and archaeological monuments, and the preservation of heritage through education expresses a policy of coexistence, tolerance and interaction between multiple cultures, a link between the past and the present, and a development vision for the future.The research sheds light on the contribution of educational institutions and specialized colleges in the field of professional and vocational development of local communities, which is positively reflected in the maintenance, restoration and preservation of historic centers and cities.